Substernocleidomastoid Muscle Neck Lipoma: An Isolated Case Report - Ferdinand Rico; Dustin Hoang; John Lung; Olivia Puccio; Michelle Brito; M. Haris Nazim; Alan Sbar (Case Reports in Surgery)
Introduction. We report this large neck mass, located behind the sternocleidomastoid (SCM) within the posterior cervical space and anterior to the prevertebral fascia. The mass is displacing the carotid sheath and its neurovascular contents medially. It extends almost the whole length of the SCM muscle all the way down to the lung apex. Case Presentation. A 30-year-old female patient presented to our clinic with a left anterior neck mass for a few months with dysphagia. The lipoma was excised completely along with level II to IV lymphadenectomy. A very small volume chyle leak was noted intraoperatively. The drain was removed 2 weeks later only to recur in one month. A new drain was placed by interventional radiology, and the drainage resolved completely. Discussion. The patient with mild dysphagia had a lipoma large enough to push vital structures away from their normal anatomical position. Due to the difficult location and the size of the lipoma, a meticulous formal lateral neck dissection was required. A 3D imaging like CT or MRI would be helpful to preoperatively plan the dissection. Substernocleidomastoid neck lipoma in our case is a rare benign tumor that was challenging to excise.